The Effect of Rationalization of Land Use on the Inland Excess Water (Water Logging) Hazard in Hungary's Plain Areas - Körösparti, János Tamás; Kajári, Balázs; Kerezsi, György; Túri , Norbert; Pásztor, László; Bozán, Csaba (Journal of Central European Green Innovation, 2022)
Excess water (water logging) hazard is the random variable that indicates the probability of excess ater inundation in a given area. In this article, we present the effects of the change in land use and the rationalization of land use on the degree of excess water hazard. The effect of suspending the cultivation of areas with unfavorable water management and changing land use (e.g. afforestation, turning non-flowing areas into reservoirs, greening, etc.) is determined based on trend studies, using the CORINE and NÖSZTÉP databases. The land use class values ​​used for excess water hazard mapping have been modified to show the effect of the assumed change in land use. During the analysis, we took into account areas that lie deeper than their surroundings (~450 thousand ha) and are highly hazarded areas. In the lowland areas, the change seems to be small, but if we compare it to the low-lying areas, the rationalization of land use reduced the areas' vulnerability to inland excess water by 12.13% and increased it by 8.42%. According to our findings, the tendency to inland excess water created by the natural features of individual agricultural areas can be demonstrably reduced by land use that takes water management conditions into account. Based on all of this, it can be stated that during farming, the cultivation branches must be adapted to the soil and water management features.
Keywords: inland excess water; vulnerability; land-use; random forest; scenario